The Role Analysis of the Physical Environment, Socio-Economic, and the Urgency of Tat Tvam Asi in Collective Resource Management Multicultural Subak - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi; Wahyuni, Ni Komang Surya (APMBA (Asia Pacific Management and Business Application), 2022)
This study aims to determine the effect of the role of the physical environment, socio-economics and the urgency of governance on the management of multicultural subak collective resources. The type of research is quantitative. The sampling technique used was a random sampling technique determined by the slovin formula—data collection techniques in distributing questionnaires and measured using a Likert scale. The study was conducted in Subak spread across the province of Bali by adhering to multiculturalism, and the sample used in the study was 170. Data or statistical analysis techniques in the study were considered using the Structural Equation Model (SEM) with WarpPLS 5.0 software modelling. The results show that the role of the physical environment does not have a significant effect on the management of the multicultural subak collective resources. In contrast, socio-economics and the urgency of governance significantly affect the management of the multicultural subak collective resources. This research focuses on multicultural subak, which contains the concept of Tri Hita Karana, which includes Parhyangan, Pawongan and Palemahan and Tat Tvam Asi is an embodiment of love for all beings. These two concepts link the subak organisation to continue to manage spiritually-based collective resources.